Analysis of Students' Mathematical Communication Skills In Terms of Self-Confidence - Novianti Fay; Urni Babys; Netty Julinda Marlin Gella (CV. AFDIFAL MAJU BERKAH, 2022)
Mathematical communication skills are the ability to convey mathematical ideas or ideas orally or in writing, and to understand and accept other people's ideas or ideas carefully, analytically, critically, and evaluative to sharpen the understanding. The purpose of this study is to analyze students ' mathematical communication skills in terms of self-confidence. The study was conducted in SMP Negeri 3 Soe with the subject of research being VIII grade students as many as 22 students. This study uses the qualitative descriptive method. Data collection techniques in the form of tests, questionnaires, and interviews. The data analysis follows the miles and Huberman model. The results showed that students ' mathematical communication skills are seen from different levels of confidence. Students who have a high level of confidence can meet 4 indicators of mathematical communication skills, namely connecting real objects, images, and diagrams into mathematical ideas; able to present ideas in the form of images; able to use terms, mathematical symbols, and structures to present ideas, describe relationships and model making; able to understand, interpret and evaluate mathematical ideas. Students who have a moderate level of confidence can meet three indicators, namely connecting real objects, images, and diagrams into mathematical ideas; being able to present ideas in the form of images; able to use terms, mathematical symbols, and structures to present ideas, describe relationships and model making. Students with a low level of confidence are only able to meet one indicator, namely in using terms, mathematical symbols, and structures to present ideas, describe relationships, and model making.